APPLICABILITY OF THE NON STEROID ANTIINFLAMMATORY DRUGS IN FEVER THERAPY OF CHILDREN - O.A. Mubarakshina (Union of pediatricians of Russia, 2008)
The non steroid anti-inflammatory drugs are widely applied in the pediatric practices for the fever therapy among children. While choosing the medications from this group to prescribe them to the children, it is essential to get guided towards the highly efficient medications with the least risk of the side effects. Only Paracetamol and ibuprofen are fully compliant with this requirement. They are officially recommended by who as the anti febrile medications for use in pediatrics. In the given article, the author reviews the advantages of ibuprofen over to Paracetamol based on the data from the foreign randomized research. She pays certain attention to the safety issues during the ibuprofen based treatment and to the opportunities of the combined Paracetamol and ibuprofen based therapy.Key words: fever, treatment, non steroid anti-inflammatory drugs, children.